Breaking Binaries? Biomedicine and Serostatus Borderlands among Couples with Mixed HIV Status. Issue 8 (17th November 2017) - Persson, Asha; Newman, Christy E.; Ellard, Jeanne
ABSTRACT: With recent breakthroughs in HIV treatment and prevention, the meanings of HIV-positivity and HIV-negativity are changing at biomedical and community levels. We explore how binary constructions of HIV serostatus identities are giving way to something more complex that brings both welcome possibilities and potential concerns. We draw on research with couples with mixed HIV status to argue that, in the context of lived experiences, serostatus identities have always been more ambiguous than allowed for in HIV discourse. However, their supposed dichotomous quality seems even more dubious now in view of contemporary biomedical technologies. Invoking the anthropological concept of "borderlands, " we consider how biomedicine is generating more diverse serostatus identities, widening the options for how to live with HIV, and eroding the stigmatizing serostatus binary that has haunted the epidemic. But we also ask whether this emerging borderland, and its "normalizing" tendencies, is concomitantly giving rise to new and troubling binaries. Abstract :